Experimental and numerical study of two underwater explosion bubbles: Coalescence, fragmentation and shock wave emission. (15th October 2019) - Li, Shuai; Zhang, A-Man; Han, Rui; Cui, Pu
Abstract: This work presents experimental and numerical investigations on the nonlinear interaction, coalescence, collapse and rebound of two pulsating bubbles, which are generated by underwater explosions (2.5 g PETN for each). The transient physical phenomena are captured by a high-speed camera and the near-field pressure signals measured by pressure sensors. The boundary integral simulations gain further insight into the high-speed liquid jet formation, jet impact, splash, fragmentation, and the associated flow field characteristics. Particularly, the numerical simulation reproduces the multiple splits of the coalesced bubble, which partly reveals the mechanism of the bubble cloud formation. These sub-bubbles collapse with different velocities and reach their minimum volumes at different times, leading to the emission of multiple bubble pulse pressures (shock waves) at the final collapse phase. Interestingly, we find that the last pressure peak is the largest one for non-axisymmetric configurations, which is attributed to the asymmetric collapse of the coalesced bubble about the centerline of the two bubbles at inception. More specifically, the lower bubble segments collapse earlier and generate large pressure waves, which further drives the remaining part of the bubble to collapse more violently. We also make quantitative comparisons of the pressure impulse between different configurations. Highlights: The coalescence of two underwater explosion bubbles is experimentally studied. The numerical simulation reveals the mechanism of the bubble cloud formation. Quantitative comparisons of the pressure impulse between different cases are made. Multiple bubble pulse pressures are emitted and the last peak is the largest.